2022
DOI: 10.1038/s41598-022-08242-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of psychopathology on academic performance in school-age children and adolescents

Abstract: Psychiatric symptoms have consistently been associated with negative educational outcomes. However, possible confounding variables, such as comorbid mental and environmental conditions, have not been well addressed. This study examined whether mental health problems were significantly linked to academic performance in a Spanish school-based sample, after adjustment for co-occurring psychiatric symptoms and multiple contextual factors. Parents completed a questionnaire regarding child’s sociodemographic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Our findings also supported the hypothesis that ADHD would increase the risk for academic impairment and are consistent with previous literature, showing that youth with ADHD experience a variety of academic difficulties, including poor grades, low academic achievement, special education need, grade retention and failure to complete high school, even after adjusting for intelligence, SES, and learning disabilities (10,11,65). Interestingly, though, the present study confirms for the first time the association between ADHD diagnosis and academic performance in Spain and supports a prior analysis conducted by Pagerols et al (33), which found that students with increased levels of attention problems were more likely to perform poorly, regardless of other risk factors such as comorbid psychopathology, sociodemographic characteristics, stressful events, and lifestyle behaviors (33). Moreover, the current investigation showed that SLD contributed independently to heighten the risk of academic underachievement, especially for language subjects, suggesting that learning disorders may compromise the academic performance of students by impeding or slowing their acquisition of knowledge through reading (22).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings also supported the hypothesis that ADHD would increase the risk for academic impairment and are consistent with previous literature, showing that youth with ADHD experience a variety of academic difficulties, including poor grades, low academic achievement, special education need, grade retention and failure to complete high school, even after adjusting for intelligence, SES, and learning disabilities (10,11,65). Interestingly, though, the present study confirms for the first time the association between ADHD diagnosis and academic performance in Spain and supports a prior analysis conducted by Pagerols et al (33), which found that students with increased levels of attention problems were more likely to perform poorly, regardless of other risk factors such as comorbid psychopathology, sociodemographic characteristics, stressful events, and lifestyle behaviors (33). Moreover, the current investigation showed that SLD contributed independently to heighten the risk of academic underachievement, especially for language subjects, suggesting that learning disorders may compromise the academic performance of students by impeding or slowing their acquisition of knowledge through reading (22).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, demographic characteristics such as gender, SES, stressful events (e.g., adoption, parental divorce/separation, grade retention), and lifestyle behaviors (e.g., diet, screen time, sleep duration) are also important variables that affect academic performance in children (30)(31)(32)(33)(34)(35). In particular, school failure and poor academic achievement are strongly related to socioeconomic factors operating at individual and community levels (36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it may be a third force that is not being captured in the Western measures being used in PISA (although they have been regionally validated); that is, the unity between mind, body, community, and spiritual aspects of the region (Joshanloo et al, 2021 ), which has not yet been captured or investigated by education authorities either (OECD, 2021 ). School factors that produce low academic performance may also fuel mental health concerns, especially as one drives the other (Agnafors et al, 2021 ; Deighton et al, 2018 ; Pagerols et al, 2022 ; Riglin et al, 2014 ). Alternatively, issues identified in UAE public schools, i.e., non-national teachers, low status of teaching, low teacher wellbeing, few resources, and little parent support (Marquez et al, 2022b ) may contribute.…”
Section: Resultsmentioning
confidence: 99%
“…Existing literature has scrutinized the role of mental disturbance in educational performances and achievements and highlighted that disorders in psychiatric conditions might be a salient negative attribute in academic attainment (Eisenberg et al, 2009;Arnold et al, 2020;Agnafors et al, 2021;Pagerols et al, 2022). This exploration has been extended to the L2 learning context, and the impact of mental disturbance was further investigated on L2 learning, though only a limited number of studies were documented.…”
Section: Connecting Mental Disturbance With Second Language Learning ...mentioning
confidence: 99%